Effect of Cu2+ doping on the physicochemical properties and chromate adsorption capacity of goethite. Issue 1 (2nd January 2019) - Khan, Sadullah; Zaman, Muhammad Iqbal; Mustafa, Syed; Niaz, Abdul; Khan, Muhammad Ibrahim; Khan, Fawad
ABSTRACT: Laboratory-prepared pure and 0.32% Cu 2+ ion-doped goethite samples have been characterized for surface area, pH of point of zero charge (pHpzc ), X-ray diffraction, thermogravimetric and differential thermal analyses, transmission electron microscopy, and Fourier-transform infrared (FTIR) analysis. The analyses show that the Cu 2+ ions get incorporated into the crystals of goethite by forming a solid solution. Due to the presence of Cu 2+ ions, the surface area and pore volume of goethite are increased from 34.69 to 126.52 m 2 g −1 and from 0.02 to 0.06 cm 3 g −1, respectively. The results of chromate adsorption experiments, carried out in the concentration range 0.25–2.01 mmol.L −1, show that chromate adsorption remarkably increases at pH 3 and 5, with Cu doping in goethite, and decreases with increasing pH. However, unlike pure goethite, chromate uptake by Cu-doped goethite decreases with increasing temperature. The data of chromate adsorption by both the samples of goethite fit well into the Langmuir model. The values of isosteric heats of adsorption (Δ H ‾ ), being positive for pure goethite and negative for Cu-codoped goethite, show the processes of adsorption to be endothermic in case of pure and exothermic in case of Cu-codoped goethite. FTIR analysis reveals that innersphere complexation is the dominant mechanism for chromate adsorption by Cu-codoped goethite.